Frontispiece: Selective Calixarene‐Directed Synthesis of MXene Plates, Crumpled Sheets, Spheres, and Scrolls. Issue 34 (16th June 2017) - Vaughn, Arni; Ball, Jeremy; Heil, Tobias; Morgan, David J.; Lampronti, Giulio I.; Maršalkaitė, Gabija; Raston, Colin L.; Power, Nicholas P.; Kellici, Suela
Abstract : MXenes are a rapidly emerging new class of 2Dlaminar materials with unique properties. This work is the first example of templated morphological change beyond sheets of the thinnest member of the MXenes class of materials, Ti2 C, leading to plates, crumpled sheets, spheres and scrolls. This has been achieved by taking advantage of the inherent properties of a family of calixarene derivatives. This advancement opens up wider avenues of discovery/design for new morphologies from the wider family of MXenes beyond Ti2 C, along with opportunities to exploit any new physico‐chemical properties proffered. For more information see Communication by S. Kellici and co‐workers onpage 8128 ff. .